Transforming food waste: how immobilized enzymes can valorize waste streams into revenue streams. (December 2018) - Andler, Stephanie; Goddard, Julie
Abstract Food processing generates byproduct and waste streams rich in lipids, carbohydrates, and proteins, which contribute to its negative environmental impact. However, these compounds hold significant economic potential if transformed into revenue streams such as biofuels and ingredients. Indeed, the high protein, sugar, and fat content of many food waste streams makes them ideal feedstocks for enzymatic valorization. Compared to synthetic catalysts, enzymes have higher specificity, lower energy requirement, and improved environmental sustainability in performing chemical transformations, yet their poor stability and recovery limits their performance in their native state. This review article surveys the current state-of-the-art in enzyme stabilization & immobilization technologies, summarizes opportunities in enzyme-catalyzed valorization of waste streams with emphasis on streams rich in mono- and disaccharides, polysaccharides, lipids, and proteins, and highlights challenges and opportunities in designing commercially translatable immobilized enzyme systems towards the ultimate goals of sustainable food production and reduced food waste.